2014
DOI: 10.1523/jneurosci.4105-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity Strength of Dissociable Striatal Tracts Predict Individual Differences in Temporal Discounting

Abstract: Large individual differences exist in the ability to delay gratification for the sake of satisfying longer-term goals. These individual differences are commonly assayed by studying intertemporal preferences, as revealed by choices between immediate and delayed rewards. In the brain, reward-based and goal-oriented decisions are believed to rely on the striatum and its interactions with other cortical and subcortical networks. However, it remains unknown which specific cortical-striatal tracts are involved in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
127
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 71 publications
12
127
1
Order By: Relevance
“…Finally, whereas functional connectivity between medial prefrontal cortex, amygdala, and striatum has been shown to mediate avoidance learning (43), it did not mediate learning biases in our task, suggesting that such connectivity might be equally involved in learning from increases and decreases in aversive outcomes. Several reports have linked variations in the structure of the striatum to individual differences in healthy and pathological decision-making behavior (46,47) and to the expression of certain pain disorders (48,49). Of particular relevance to the present study is the observation that obsessive-compulsive disorder (OCD), which features compulsive harm-avoidance behavior, is associated with higher gray matter density in the putamen (50).…”
Section: Discussionmentioning
confidence: 71%
“…Finally, whereas functional connectivity between medial prefrontal cortex, amygdala, and striatum has been shown to mediate avoidance learning (43), it did not mediate learning biases in our task, suggesting that such connectivity might be equally involved in learning from increases and decreases in aversive outcomes. Several reports have linked variations in the structure of the striatum to individual differences in healthy and pathological decision-making behavior (46,47) and to the expression of certain pain disorders (48,49). Of particular relevance to the present study is the observation that obsessive-compulsive disorder (OCD), which features compulsive harm-avoidance behavior, is associated with higher gray matter density in the putamen (50).…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have shown that discount rates are not only associated with regional changes within the valuation and control networks, but also depend on the strength of connections within and between these networks (31). For instance, we recently showed that frontostriatal tracts predicted decreased delay discounting, whereas subcorticostriatal tracts predicted increased delay discounting in adults (21).…”
Section: Significancementioning
confidence: 80%
“…Research suggests that multiple cognitive and neural processes underlie delay discounting (18)(19)(20). On the one hand, more impatient behavior can result from oversensitivity to immediate rewards (21). For example, there are several studies that show that people are more impatient when an immediate option is present compared with when both options are in the future (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger structural and functional connectivity between striatum and lateral pFC has been linked to greater patience across individuals ( Van den Bos, Rodriguez, Schweitzer, & McClure, 2014), and functional connectivity is influenced by dopamine: Pharmacologically increasing dopamine in pFC affects connectivity with the striatum in intertemporal choice (Kayser et al, 2012), and functional connectivity between striatum and lateral pFC during rest is enhanced by L-dopa relative to placebo (Kelly et al, 2009). Thus, enhanced connectivity through dopaminergic medication could also contribute to the results we report here.…”
Section: Locus Of Dopamine Effectsmentioning
confidence: 99%